Quality analysis of water used for irrigation in rural property of Cravolândia, BA, Brazil (Research, Society and Development, 2022)
The quality of water resources is an important aspect for irrigated agriculture and the problems related to water quality have been studied over time, with the results highlighting issues related mainly to its salinity. The concentration of salts and ions in water can considerably alter the characteristics of planting, soil and plant development. The objective of this study was to evaluate, through multivariate statistical analysis, the water quality of the Jiquiriçá River Watershed used for irrigation in rural properties in Cravolândia-BA. Two campaigns in different periods were conducted at nine surface points water that serve for irrigation practices. The analyzes were performed and compared with the values established mainly by Resolution No. 357/2005 of the National Council for the Environment - CONAMA. Through multivariate analysis, it was found that electrical conductivity, sodium, total solids and iron had the greatest influence on the segregation of the sample groups. By employing principal component analysis, it was found that two factors explained more than 70% of the total variance. It is concluded that among the nine points sampled, two of them, located on the Olhos d'água River, presented results that did not comply with the legislation for the following parameters of evaluation of water quality: color, total solids, iron, electrical conductivity and sodium. For these points, detailed studies are necessary for the adequate choice of cultures more resistant to salinity.